PENERAPAN METODE GEOGRAPHICALLY WEIGHTED REGRESSION PADA TINGKAT PENCEMARAN AIR BERDASARKAN TOTAL COLIFORM DI PROVINSI JAMBI - Fitriyani Fitriyani; Sherli Yurinanda; Cut Multahadah (LPPM Universitas Bina Bangsa, 2023)
The purpose of this study is to obtain a local estimation model formed by considering spatial factors on the level of water pollution based on total coliforms in Jambi Province and can determine the most dominant factors affecting the total coliform water of PDAM Districts / Municipalities in Jambi Province using Geographically Weighted Regression (GWR) analysis. The type of data used in this study is primary data in quantitative form. This primary data was obtained by taking PDAM water samples directly in 9 regencies/cities in Jambi Province. The results of GWR analysis show that the dominant factors affecting the total coliform of PDAM water in each district/city in Jambi Province vary with different estimated parameters. The best model formed is a model with the GWR method, the adaptive bisquare weighting function which is shown from the value of the model's goodness criteria, namely the smallest AIC value and the largest coefficient of determination